2013
DOI: 10.1016/j.cct.2013.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Growing Right Onto Wellness (GROW): A family-centered, community-based obesity prevention randomized controlled trial for preschool child–parent pairs

Abstract: Growing Right Onto Wellness (GROW) is a randomized controlled trial that tests the efficacy of a family-centered, community-based, behavioral intervention to prevent childhood obesity among preschool-aged children. Focusing on parent-child pairs, GROW utilizes a multi-level framework, which accounts for macro (i.e., built-environment) and micro (i.e., genetics) level systems that contribute to the childhood obesity epidemic. Six hundred parent-child pairs will be randomized to a 3-year healthy lifestyle interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
98
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 64 publications
(98 citation statements)
references
References 68 publications
0
98
0
Order By: Relevance
“…30,31 The Institutional Review Board (IRB) Human Subjects Committee at the University of Minnesota and Vanderbilt University approved all protocols used in NET-Works GROW Study, respectively. All participants signed written informed consent prior to participation into the respective studies.…”
Section: Methodsmentioning
confidence: 99%
“…30,31 The Institutional Review Board (IRB) Human Subjects Committee at the University of Minnesota and Vanderbilt University approved all protocols used in NET-Works GROW Study, respectively. All participants signed written informed consent prior to participation into the respective studies.…”
Section: Methodsmentioning
confidence: 99%
“…We conducted a cross-sectional analysis of baseline data collected from parent–child pairs enrolled in the Growing Right Onto Wellness (GROW) randomized controlled trial (clinicaltrials.gov identifier NCT01316653) of a 3-year family-centered behavioral intervention delivered in local community centers [17]. This study was approved by the Vanderbilt Institutional Review Board, and all adult participants signed informed consent prior to participating [18].…”
Section: Methodsmentioning
confidence: 99%
“…1). Full eligibility criteria have been published elsewhere [17] but included (1) 3–5 year old child; (2) child’s BMI >50th percentile and <95th percentile on standardized Center for Disease Control growth curves; (3) parent age ≥18 years; (4) parent commitment to participate in the duration of the 3-year study; (5) parent and child completion of baseline data collection; and (6) family must reside or frequently pass through one of two geographic regions in Nashville that is contiguous with a community center designated for the intervention. We included in this study only the 555 Latino parent–child pairs.…”
Section: Methodsmentioning
confidence: 99%
“…This association depends on the nature of the relationship and on the age of the individual. When he is a child, an individual is greatly influenced by the familial eating habits [4,36,[54][55][56] and physical activity behaviors [30]. In [57], the authors describe the parents' education as one of the main determinants of obesity.…”
Section: Social Factorsmentioning
confidence: 99%
“…They suggested that a higher density of fast foods (respectively park areas) in the neighborhood was correlated with an increased likelihood of overweight/obesity (respectively LTPA). In [56], the authors observed a strong association between individuals and their peers' health behavior (exercise practice, feeding habits) in young adults. Although they could not show an actual causality, they concluded that the health behavior of one's peers influences the development of a similar behavior in a young individual.…”
Section: Psychological and Behavioral Factorsmentioning
confidence: 99%